Implementation of Customer Communication to Maintain the Hospital Image from the Issues of Coviding Patients - Rain Gunawan; Muhammad Isnaini (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2021)
Accusations of hospitals that have taken Indiscipline’s actions on Covid-19 cases have many comments that’s appeared on social media like Twitter with the hashtag #BongkarMafiaCovidRS which reached 5,700 tweets. This study aims to examine the accusations of this issue, how the issue started and how to dismiss it. This research is a qualitative research using literature method. To complement the results of this study, the researcher also conducted interviews with several informants from medical personnel who worked in the hospital. Does the issue of coviding patients make the hospital's image worse? How is the hospital able to maintain the image of the hospital as a good health service facility amid accusations of coviding patients? The results of this study indicate that the developing issue is not based on facts, the hospital has clear SOPs and guidelines in carrying out covid-19 patient care. The hospital also conducts and implements customer communication to patients and patients' families before the procedure so that patients and families are well educated. Implementation of customer communication is one of the strategies that are believed to be able to maintain the hospital image and ward off accusations of the issue of coviding patients.